High-quality AlInN/GaN distributed Bragg reflectors grown by metalorganic vapor phase epitaxy. (26th November 2020) - Akagi, Takanobu; Kozuka, Yugo; Ikeyama, Kazuki; Iwayama, Sho; Kuramoto, Masaru; Saito, Tatsuma; Tanaka, Takayuki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Iwaya, Motoaki; Akasaki, Isamu
Abstract: We obtained a high-quality 40-pair AlInN/GaN distributed Bragg reflector with a high growth rate of the AlInN layers (500 nm h −1 ), showing almost no threading dislocations and a peak reflectivity of 99.9% at 413 nm, by using a 0.3 nm GaN cap layer grown on the AlInN layer at low growth temperature. We also found that the threading dislocations generated at the interfaces between the bottom AlInN and the top GaN in the cases of 5–10 nm GaN cap layers which were typically used. Excess In atoms on the AlInN surfaces seem to cause the generation of the threading dislocations.